2005
DOI: 10.1007/s10519-004-0855-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective Breeding for an Infant Phenotype: Rat Pup Ultrasonic Vocalization (USV)

Abstract: To examine processes underlying generational and developmental influences on anxiety, this laboratory produced two lines of (N:NIH strain) rats, selectively bred on the basis extreme rates of ultrasonic vocalization in 2 minutes of isolation at Postnatal Day 10. The research reviewed in this article focuses on: (1) establishment of the selectively bred lines; (2) defining infant behavioral and physiological phenotypes and (3) determining whether infantile USV phenotypes endure over development. The High and Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 95 publications
5
60
1
Order By: Relevance
“…Genetic variations have been shown to affect the production of USVs (Brunelli;Brunelli et al, 1997;Burgdorf et al, 2005;Hahn et al, 1987;Sales & Smith, 1978), but there have been few studies of the possible influence of genetic and environmental variables in determining reactivity to these social signals (see Allen et al, 2007;Brudzynski, 2007;Endres et al, 2007). Although the stimuli used in Experiment 1 were equally neutral, as measured by unconditional freezing, they might differ in terms of salience or efficacy as cues supporting fear conditioning.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic variations have been shown to affect the production of USVs (Brunelli;Brunelli et al, 1997;Burgdorf et al, 2005;Hahn et al, 1987;Sales & Smith, 1978), but there have been few studies of the possible influence of genetic and environmental variables in determining reactivity to these social signals (see Allen et al, 2007;Brudzynski, 2007;Endres et al, 2007). Although the stimuli used in Experiment 1 were equally neutral, as measured by unconditional freezing, they might differ in terms of salience or efficacy as cues supporting fear conditioning.…”
Section: Methodsmentioning
confidence: 99%
“…The USV lines were created to produce a developmentalgenetic model system. The hypothesis is that autonomic and behavioral temperamental differences in infancy might cause behavioral or autonomic nervous system dysfunction in adulthood [33]. The results appear to be encouraging because the USV High and Low lines selected for different rates of USV in response to isolation during infancy and tested during adulthood presented reliable differences in several animal models, such as the open field, social interaction test, and elevated plus maze.…”
Section: The Linkage Of Emotional Traitsmentioning
confidence: 88%
“…To investigate generational and developmental variables associated with anxiety, Brunelli et al [32,33] reported the creation of two lines of rats selected for different rates of USVs in response to isolation. Rat pups were screened at 10 ± 1 days of age in a 2 min isolation test.…”
Section: High and Low Ultrasonic Vocalization Ratsmentioning
confidence: 99%
“…Various issues related to the neurochemical control of crying remain to be resolved, including the potentiation of crying when the mother is nearby (e.g., [107]). The growing availability of molecular genetic techniques applied to behavioral phenotypes opens up a huge research area for study, particularly with respect to the role of specific genes in regulating crying and cry responsivity, and the interaction of genetic and environmental factors, e.g., [14]. It is my hope that the present review will serve a useful role in focusing attention on the importance of the cry circuit in mammalian evolution, and help to stimulate a range of future studies.…”
Section: Suggestions For Future Studiesmentioning
confidence: 94%